2010
DOI: 10.1074/jbc.m110.117044
|View full text |Cite
|
Sign up to set email alerts
|

Novel Importin-α Family Member Kpna7 Is Required for Normal Fertility and Fecundity in the Mouse*

Abstract: Nuclear importing system and nuclear factors play important roles in mediating nuclear reprogramming and zygotic gene activation. However, the components and mechanisms that mediate nuclearly specific targeting of the nuclear proteins during nuclear reprogramming and zygotic gene activation remain largely unknown. Here, we identified a novel member of the importin-␣ family, AW146299(KPNA7), which is predominantly expressed in mouse oocytes and zygotes and localizes to the nucleus or spindle. Mutation of Kpna7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 53 publications
(71 reference statements)
4
84
1
1
Order By: Relevance
“…A recent study identified the PRDM14 expression by microarray assay, in particular, undifferentiated human ESCs (14), and Chia et al (15) described it as an important transcription factor in human pluripotency maintenance. HU stated that PLK1, a polo-like kinase family member, was involved in cell mitosis and also expressed in a high significant manner in many of human malignancies so it is considered a carcinogenic gene (16).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified the PRDM14 expression by microarray assay, in particular, undifferentiated human ESCs (14), and Chia et al (15) described it as an important transcription factor in human pluripotency maintenance. HU stated that PLK1, a polo-like kinase family member, was involved in cell mitosis and also expressed in a high significant manner in many of human malignancies so it is considered a carcinogenic gene (16).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence, including phenotypes of KPNA knockout mouse models, suggests there may be a corresponding role for this protein family in the female germline. KPNA7 is expressed in oocytes and appears to be important for pre-implantation development with parthogenetically activated eggs from conditional mutants failing to develop to the blastocyst stage (Hu et al 2010). The absence of KPNA1, also known as importin a5, leads to reduced numbers of growing follicles and hypoplasia of the reproductive tract in mice (Moriyama et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…27,28 In mice, truncating mutations resulted in reduced reproductive potential and female lethality. 25 These expression patterns are interesting as one of our subjects had ambiguous genital findings both at birth and on subsequent examination, without identifiable endocrine disturbance. The family member KPNA2 is a binding partner of the androgen receptorinteracting protein 3 (Arip3).…”
Section: Discussionmentioning
confidence: 78%
“…In the mouse KPNA7 may interact with KPNB1. 25 Mutations in the nuclear localization sequence of ARX are associated with both infantile spasms and lissencephaly, and result in abnormal subcellular distribution of the protein product. 26 As loss-of-function mutations in ARX cause a spectrum of infant-onset epilepsy disorders, this observation further supports the concept that nuclear concentrations of ARX proteins might be compromised by reduced activity of the import machinery.…”
Section: Discussionmentioning
confidence: 99%